Clinimetric Properties of the Fragile X‐associated Tremor Ataxia Syndrome Rating Scale. Issue 2 (22nd January 2019) - Hall, Deborah A.; Stebbins, Glenn T.; Jacquemont, Sebastien; Berry‐Kravis, Elizabeth; Goetz, Christopher G.; Hagerman, Randi; Zhang, Lin; Leehey, Maureen A.
ABSTRACT: Background: There are currently no proven treatments for fragile X‐associated tremor and ataxia syndrome (FXTAS). Validated outcome measures are needed in order to plan and conduct clinical trials to aid in the development of therapy. Methods: This study examined the reliability and construct validity of the FXTAS Rating Scale. The study was conducted by using ratings from movement disorder specialists, who were blinded to gene status, on the FXTAS Rating Scale. Results: In 295 premutation carriers with and without FXTAS, 33 scale items showed a high level of overall reliability, adequate item‐to‐total correlations and construct validity. Factor analysis revealed four components. Conclusions: The result demonstrates that many items in the scale meet standard clinimetric criteria, but modification of the scale improved the overall utility.